2005
DOI: 10.1007/s10464-005-6235-4
|View full text |Cite
|
Sign up to set email alerts
|

Family Support and Mental Health in Pregnant Women Experiencing Interpersonal Partner Violence: An Analysis of Ethnic Differences

Abstract: This study investigated the relationship between family support and mental health in a community sample of pregnant women experiencing interpersonal partner violence (IPV). This study also examined how family support may differentially affect mental health in Black and White women experiencing IPV. A total of 110 participants (32 Black and 78 White) were obtained from the first time period of a longitudinal study examining the effects of domestic violence on women. The model was supported (chi2 = 142.55; df = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…A study that focused on the key features of the transition to parenthood found that significant numbers of low risk parents experience psychological stress during this time, and that their concerns were much broader than the issues addressed by traditional ante-natal classes. 1 Respondents identified their mothers, husbands and sisters as people to depend on and listen to for good advice, help and loved. The findings of this study showed majority of respondents had support from husbands, mothers, mothers-in-law and fathers-in-law.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study that focused on the key features of the transition to parenthood found that significant numbers of low risk parents experience psychological stress during this time, and that their concerns were much broader than the issues addressed by traditional ante-natal classes. 1 Respondents identified their mothers, husbands and sisters as people to depend on and listen to for good advice, help and loved. The findings of this study showed majority of respondents had support from husbands, mothers, mothers-in-law and fathers-in-law.…”
Section: Discussionmentioning
confidence: 99%
“…Couples who were strongly united and romantic in their relationship before the pregnancy found it harder to adapt to parenthood than those whose relationships were already faltering. 1,2 Unfortunately for some couples, their relationship does not always recover as around 14% of couples split up before the baby was born. Preparing parents for parenthood by addressing the emotional changes that take place during this period, and helping parents to address the problems that occur is therefore paramount.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other determinants include individual characteristics, such as negative cognitive style and low self-esteem (Leigh & Milgrom, 2008), maternal age and past history of mood disorders (Milgrom et al, 2008). Additionally, factors such as financial difficulties, employment conditions (Rich-Edwards et al, 2006), low social support and strain in intimate relationships (Jones, Bogat, Davidson, von Eye, & Levendosky, 2005;Lee et al, 2007), major life events and partner violence (Leigh & Milgrom, 2008;Stone et al, 2015) have been suggested as potential risk factors. However, there is no conclusive evidence to support that any of these factors alone contribute to the development of antenatal distress.…”
Section: Overviewmentioning
confidence: 99%